Students' attitudes towards statistics study on a sample of students of the faculty of education Tishreen University (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current study aimed to identify the attitudes of a sample of students of the Faculty of Education Tishreen University towards the statistics subject they study in the first and second year, and as an important subject in the completion of research seminars and graduation projects, as it requires them to complete the practical side using the statistical methods they studied.To achieve the objectives of the study, the researcher relied on the descriptive approach, and a random sample of 270 male and female students was selected, divided into three disciplines (class teacher, psychological counseling, and curricula) during the academic year 2021/2022. The researcher also relied on the Attitudes towards Statistics Scale prepared by Al-Smadi (2008), and the scale in its final form consists of (29) items distributed over five dimensions. The results indicated that there were no differences between males and females in their attitude towards statistics, while there were statistically significant differences between the sample members in their attitude towards statistics due to the variable of specialization in favor of the class teacher division in the performance dimension.